PENGARUH KUALITAS PELAYANAN, SUASANA RESTO DAN HARGA TERHADAP KEPUASAN PELANGGAN: Studi Kasus di SUSHI TEI Surabaya - Niawati, Niawati; Hesti Pandu Widodo; Achmad Daengs GS (Jurnal Mahasiswa Manajemen dan Akuntansi, 2022)
A very important role for a trading or service company is marketing. An attractive marketing strategy is to be able to maintain advantages, improve the quality of products and services as well as prices that are appropriate in the eyes of customers. In order to maintain the business cycle, service companies must pay attention to the quality of service and the atmosphere of the restaurant so that customers feel comfortable. The type of research used is descriptive research. This research was conducted on 100 respondents of Sushi Tei Ciputra World Surabaya customers. The sampling technique used in this study is the incidental technique. The data analysis techniques used are (1) validity and reliability test of the questionnaire items, (2) multiple linear regression test. Then the regression model is tested for the hypothesis that is simultaneously (F test), partially (t test) and the dominant variable. This study aims to explain the causal relationship between service quality factors, restaurant atmosphere factors and price factors on customer satisfaction through hypothesis testing. Based on hypothesis testing, it was obtained that simultaneously the service quality factor, restaurant atmosphere factor and price factor had an influence on customer satisfaction of 14.394. And when viewed from the Adjusted R Square that is equal to 28.9%, while based on the t test (partially) the component of the service quality variable that dominantly affects customer satisfaction is 0.450.